Effect of High Density Lipoprotein Cholesterol on the Relationship of Serum Iron and Hemoglobin with Kidney Function in Diabetes - Williams, Ashley N. (J Diabetes Complications, 2017)
Findings of increased hemoglobin inside the HDL proteome among persons with diabetes who have haptoglobin 2-2 genotype suggests that iron-induced lipid peroxidation may be involved in diabetic kidney disease. We investigated the relationships of serum hemoglobin and iron with kidney function, and whether this varied by level of HDLc, in 5,296 adults with and 49,161 without diabetes. Estimated eGFR was our marker of kidney function. Hemoglobin was positively associated with eGFR among those with diabetes and inversely among those without diabetes (interaction p-value <0.0001). Iron was inversely associated with eGFR regardless of diabetes status. When stratified by median HDLc and median hemoglobin, among persons with diabetes mean eGFR was highest in those with high hemoglobin and low HDLc and lowest in those with both low hemoglobin and low HDLc. This divergent relationship was not observed in the non-diabetic population. In contrast to hemoglobin, high iron and low HDLc was associated with a lower mean eGFR regardless of diabetes status. Our data suggests that among persons with diabetes, both hemoglobin and iron are harmful to kidney function at high levels. Our data also suggests that HDLc may play a role in the relationship of high hemoglobin in kidney function in diabetes.